ANALISIS PEMAHAMAN INFORMASI KARIER PADA PESERTA DIDIK KELAS XI SMA NEGERI 4 PONTIANAK - Ardhini, Merry; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractCareer information is a service specifically aimed at helping students, regarding further education after graduating from school, as well as helping make appropriate career choices and decisions. This study aims to analyze the understanding of career information in class XI students of SMA Negeri 4 Pontianak. The method used is descriptive method with survey research. Data collection techniques in this study are indirect techniques, data collection tools in this study are questionnaires. Data analysis using percentage analysis techniques, the population in this study amounted to 326 students, the sample in this study amounted to 25% or 87 students and was randomly selected. Based on the results of data analysis, it can be said that the understanding of students of class XI of SMA Negeri 4 Pontianak achieved an actual score of 2296 and an ideal score of 2610, meaning that reaching 87.96% was in the "Very Good" category which meant students could understand themselves, understand their environment, understand the obstacles, and can plan the future well.Â Keywords: Career, Career Information, Career Understanding